Evidence for Therapeutic Patient Education Interventions to Promote Cardiovascular Patient Self-Management: A Scientific Statement for Healthcare Professionals From the American Heart Association. Issue 6 (June 2017) - Barnason, Susan; White-Williams, Connie; Rossi, Laura P.; Centeno, Mae; Crabbe, Deborah L.; Lee, Kyoung Suk; McCabe, Nancy; Nauser, Julie; Schulz, Paula; Stamp, Kelly; Wood, Kathryn
Abstract : Background—: The burden of cardiovascular disease as a chronic illness increasingly requires patients to assume more responsibility for their self-management. Patient education is believed to be an essential component of cardiovascular care; however, there is limited evidence about specific therapeutic patient education approaches used and the impact on patient self-management outcomes. Methods and Results—: An integrative review of the literature was conducted to critically analyze published research studies of therapeutic patient education for self-management in selected cardiovascular conditions. There was variability in methodological approaches across settings and disease conditions. The most effective interventions were tailored to individual patient needs, used multiple components to improve self-management outcomes, and often used multidisciplinary approaches. Conclusions—: This synthesis of evidence expands the base of knowledge related to the development of patient self-management skills and provides direction for more rigorous research. Recommendations are provided to guide the implementation of therapeutic patient education in clinical practice and the design of comprehensive self-management interventions to improve outcomes for cardiovascular patients.